Stimulation of calcium efflux from rat liver mitochondria by adenosine 3′5′ cyclic monophosphate - Arshad, Juzu Hayati; Holdsworth, Eric S. (Springer, 1980)
The uptake or release of Ca2+ from rat liver mitochondria was studied by means of a sensitive Ca-electrode. It was found that using palmitoyl coenzyme A together with carnitine and ATP as substrates that Ca2+ was released gradually from mitochondria by adenosine 3'5' cyclic monophosphate. The effect was obtained with either mitochondria preloaded with Ca2+ or with their physiological content of Ca2+. No such release was obtained with the usual substrates used to provide energy for Ca2+ uptake by mitochondria.